Revitalizing Tradition: The Role of the Erhu in Modern Music and Global Culture - Yuan Qiaoyi (Ilmu Inovasi Nusantara, 2024)
The Erhu, one of China’s most iconic traditional instruments, is a two-stringed bowed instrument with over a millennium of history. However, in the modern era, there are challenges in maintaining the popularity and relevance of the Erhu amidst the rapid development of new musical instruments and genres. This review explores the Erhu's construction, performing techniques, historical development, and influence on modern music and contemporary culture, focusing on its role in traditional Chinese music and its contributions to international music. The methodology employed in this study involves a comprehensive literature review, incorporating academic sources, musicology books, journal articles, and interviews with professional Erhu players. A comparative analysis was also conducted to understand Erhu’s position in Western classical music and its resurgence in global popular culture. The findings indicate that, despite challenges in sustaining its existence, the Erhu continues to hold strong appeal due to its expressive sound and distinctive tonal qualities. The instrument plays a significant role in traditional Chinese music and has also been adopted in contemporary and popular music, gaining recognition in Western classical compositions. However, challenges remain in enhancing the global recognition of the Erhu outside of its original cultural context. The study recommends promoting the Erhu through cross-cultural music education and fostering collaborations between traditional and modern musicians. Moreover, technological innovations in the design and playability of the Erhu could help broaden its appeal to younger generations and expand its presence on the global music stage.